ANALISIS KINERJA PEGAWAI DI BADAN PENDIDIKAN DAN PELATIHAN PROVINSI JAWA TENGAH - Andre Dwi Cahyo; Mochammad Mustam; Zainal Hidayat (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Employee performance is a way to achieve the goal state agency. In connection with the performance, capacity and discipline employees can directly degrade the performance or improve the performance of an employee. Employees with high ability and discipline that will either make more optimal performance of employees so that they can have an impact on the overall performance of employees. However, on the contrary, if the ability of poor and working discipline is not good enough, employee performance can be optimized and bring harm to the company. This research was conducted in Central Java province TRAINING Agency. The purpose of this research was to determine the effect of ability and discipline to employee performance in TRAINING Agency Central Java province with the research method used is quantitative research. The data obtained in this study through the questioner. Analysis of the data used is the correlation coefficient Kendall and Kendall concordance coefficient. Processing the data using SPSS 16.0.